Experience with the use of mohan's valvotome for posterior urethral valve ablation at a centre in North-Eastern Nigeria - Adewale Olaotan Oyinloye; Auwal Mohammed Abubakar; Samuel Wabada; Christopher Uruku Rikin (Wolters Kluwer Medknow Publications, 2022)
Introduction: Posterior urethral valve (PUV) is the most common congenital cause of lower urinary tract obstruction in boys. Management has remained challenging in our region, with features of renal impairment evident in some patients at the time of presentation. Endoscopic valve ablation is the gold standard of treatment, but this is not readily available in our setting. Mohan's valvotome has been described as an alternative device for valve ablation. This study aimed to highlight the clinical presentation, management and early outcomes following valve ablation using Mohan's valvotome. Methods: A retrospective study of boys with PUVs managed between September 2014 and June 2018 was done. The demographic characteristics, clinical features, investigations, treatment and initial outcomes were reviewed. The main outcome measures were improved post-ablation urinary stream, serial serum creatinine values at presentation, 4-5 days of initial catheter drainage and at follow-up. Results: There were ten boys with the median age at presentation of 4 months (mean: 23.9 months; range 10 days to 7 years). Four patients presented after 1 year. All the patients had features of bladder outlet obstruction with associated fever in seven patients and urinary tract infections in six patients. Nine patients (90%) had suprapubic masses, while 2 had ballotable kidneys with co-existing urinary ascites in one patient. Valve ablation was achieved with Mohan's valvotome. There was a significant improvement in the urine stream in all patients. The median duration of follow-up was 7.5 months. Median serum creatinine was 0.95 mg/dl (mean 0.94 mg/d ± 0.38 mg/dl) at follow-up, compared to a median of 4.03 mg/dl at presentation (P = 0.01). Conclusion: Initial drainage and definitive valve ablation with Mohan's valvotome is associated with improved serum creatinine and urinary stream.